The effect of a community-based health behaviour intervention on healthcare services use among people with type 2 diabetes in Nepal - Grish Paudel; Corneel Vandelanotte; M Mamun Huda; Padam Kanta Dahal; Lal Rawal (Clinical Epidemiology and Global Health)
Background: Community-based health behavioural interventions have effectively reduced the glycated haemoglobin level (HbA1c) among individuals with type 2 diabetes mellitus (T2DM). However, there is no evidence of such interventions in improving the healthcare utilisation in under-resourced settings. Therefore, this study aimed to assess the effect of intervention in improving the visits to health facilities and specialists and reducing emergency department visits and hospital admissions among people with T2DM in Nepal. Methods: A cluster-randomised controlled trial was conducted in the Kavrepalanchowk and Nuwakot districts of Nepal, enrolling 481 people with clinically diagnosed type 2 diabetes, aged 30–70 years. A total of 30 study sites across two districts were randomly allocated into 15 intervention groups and 15 control groups. The participants in the intervention group received a community health worker and peer supporter-led health behavioural intervention for 6 months. The primary outcome of the study (health facility visits, specialist visits, emergency visits and hospital admissions) were assessed at baseline and 6 months post-intervention. Results: Intervention participants reported a higher increase in health facility visits, specialist visits, emergency visits and hospital admissions by 7.2 %, 13.5 %, 1.3 % and 0.4 % respectively, compared to control participants. However, these changes were not statistically significant. Visits to health facilities significantly increased, but only among intervention participants attending more sessions (adjusted odds ratio [AOR] = 1.16, 95 % CI:1.05–1.28). Approximately half (45.4 %) of the intervention participants attended six or fewer intervention sessions out of twelve. Conclusion: While the intervention had a positive effect on healthcare use in general, this was only significant in those with higher exposure to the intervention sessions. As such, efforts should be made that increase adherence and retention to the intervention sessions to maximise the benefit of this health behavioural intervention in improving healthcare service utilisation among individuals with type 2 diabetes in Nepal.